Aktualisasi Nilai-Nilai Pancasila Sila Kedua melalui Model Pembelajaran Demonstrasi Picture and Picture pada Siswa Madrasah Ibtidaiyah Negeri Yogyakarta I - Karimatul Hissoh (Jurnal Pendidikan Madrasah, 2021)
This study aims to know the actualization of the values of Pancasila Sila Kedua through the learning model of Picture and Picture Demonstration in Students of Madrasah Ibtidaiyah Yogyakarta I. The approach used in this study is qualitative approach with literature study method. The results showed that the implementation of the Picture and Picture demonstration alignment model was able to help students in actualizing the values of Pancasila Sila Kedua. Students become more active and can explore their abilities and can distinguish examples of pancasila practice.